2015
DOI: 10.1080/15476286.2015.1119363
|View full text |Cite
|
Sign up to set email alerts
|

AtHESPERIN: a novel regulator of circadian rhythms with poly(A)-degrading activity in plants

Abstract: We report the identification and characterization of a novel gene, AtHesperin (AtHESP) that codes for a deadenylase in Arabidopsis thaliana. The gene is under circadian clock-gene regulation and has similarity to the mammalian Nocturnin. AtHESP can efficiently degrade poly(A) substrates exhibiting allosteric kinetics. Size exclusion chromatography and native electrophoresis coupled with kinetic analysis support that the native enzyme is oligomeric with at least 3 binding sites. Knockdown and overexpression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…Immune response Roux et al (2015) ( affects the rhythmicity of the core clock oscillator mRNAs TIMING OF CAB EXPRESSION1 and CIR-CADIAN CLOCK ASSOCIATED1 (Delis et al, 2016). The second is the homodimeric DEDD-class PARNs found in plants and humans but apparently absent from budding yeast (Saccharomyces cerevisiae) and fruit flies (Drosophila melanogaster; Godwin et al, 2013).…”
Section: At1g79090mentioning
confidence: 99%
“…Immune response Roux et al (2015) ( affects the rhythmicity of the core clock oscillator mRNAs TIMING OF CAB EXPRESSION1 and CIR-CADIAN CLOCK ASSOCIATED1 (Delis et al, 2016). The second is the homodimeric DEDD-class PARNs found in plants and humans but apparently absent from budding yeast (Saccharomyces cerevisiae) and fruit flies (Drosophila melanogaster; Godwin et al, 2013).…”
Section: At1g79090mentioning
confidence: 99%
“…A similar example is the recently characterized deadenylase HESPERIN in Arabidopsis, AtHESP, which, despite exhibiting a distinct circadian expression pattern, it is not part of the core oscillator (Delis et al, 2016). AtHESP affects the expression and rhythmicity of TOC1 and CCA1 core genes.…”
Section: Destabilization and Degradation Of Mrnamentioning
confidence: 99%
“…AtHESP affects the expression and rhythmicity of TOC1 and CCA1 core genes. However, neither mRNA is a direct target of the deadenylase activity of AtHESP, suggesting that it may affect the rhythm in Arabidopsis by destabilizing one or more elusive targets (Delis et al, 2016).…”
Section: Destabilization and Degradation Of Mrnamentioning
confidence: 99%
“…However, recent in depth biochemical studies revealed that Nocturnin is a phosphatase that converts its direct substrates NADP + and NAPDH to NAD + and NADH, respectively (15,16). Hesperin (AtHESPERIN) was identified as a homologue of Nocturnin in Arabidopsis thaliana and the first deadenylase with rhythmic expression in plants (17). AtHESPERIN is oligomeric, most likely consisting of three identical subunits (17).…”
Section: Accepted Articlementioning
confidence: 99%